2021
DOI: 10.3390/toxins13050325
|View full text |Cite
|
Sign up to set email alerts
|

β-N-Methylamino-L-Alanine (BMAA) Causes Severe Stress in Nostoc sp. PCC 7120 Cells under Diazotrophic Conditions: A Proteomic Study

Abstract: Non-proteinogenic neurotoxic amino acid β-N-methylamino-L-alanine (BMAA) is synthesized by cyanobacteria, diatoms, and dinoflagellates, and is known to be a causative agent of human neurodegenerative diseases. Different phytoplankton organisms’ ability to synthesize BMAA could indicate the importance of this molecule in the interactions between microalgae in nature. We were interested in the following: what kinds of mechanisms underline BMAA’s action on cyanobacterial cells in different nitrogen supply conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 108 publications
(203 reference statements)
0
23
0
Order By: Relevance
“…BMAA showed no mutagenic, cytotoxic, or genotoxic effects on several strains of the heterotrophic bacterium Salmonella typhimurium [158]. At the same time, the photoautotrophic growth of cyanobacteria was inhibited by exogenous BMAA in micromolar amounts [104][105][106][107][108][109]159]. Moreover, the results of many published studies [57] demonstrate that BMAA was found mainly in protein-associated fractions of cyanobacterial cells.…”
Section: Bmaa and Proteins: Misincorporation And Electrostatic Bindingmentioning
confidence: 96%
See 3 more Smart Citations
“…BMAA showed no mutagenic, cytotoxic, or genotoxic effects on several strains of the heterotrophic bacterium Salmonella typhimurium [158]. At the same time, the photoautotrophic growth of cyanobacteria was inhibited by exogenous BMAA in micromolar amounts [104][105][106][107][108][109]159]. Moreover, the results of many published studies [57] demonstrate that BMAA was found mainly in protein-associated fractions of cyanobacterial cells.…”
Section: Bmaa and Proteins: Misincorporation And Electrostatic Bindingmentioning
confidence: 96%
“…The effect of BMAA has been studied mainly on various animal models and human cell cultures due to its harmful consequences for health [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. There are several studies on the effects of BMAA on plant cells [98][99][100][101][102], diatoms [103], and cyanobacteria [27,37,[104][105][106][107][108][109][110][111]. The biological actions of BMAA on eukaryotic and prokaryotic cells can be explained by various mechanisms [13,78] (Figure 3).…”
Section: Molecular Mechanisms Underlying Bmaa Toxicity 41 the Effect ...mentioning
confidence: 99%
See 2 more Smart Citations
“…As cyanobacteria are exposed to dynamic environmental conditions, they have developed sophisticated defense and detoxification systems to ameliorate the consequences of stress-induced reactive oxygen species (ROS). While the dynamics of cyanobacterial intracellular processes related to stress responses has been studied intensively ( 1 12 ), there are significant gaps in our understanding of the stresses managed in the extracellular space. In addition to a variety of exometabolites, cyanobacterial extracellular milieu is rich in proteins, whether they are actively secreted or not ( 13 18 ).…”
Section: Introductionmentioning
confidence: 99%